Effect of Cyano Substitution on Non-Fullerene Acceptor for Near-Infrared Organic Photodetectors above 1000 nm - Ha, Jong Woon; Eun, Hyeong Ju; Park, Byoungwook; Ahn, Hyungju; Hwang, Dong Ryeol; Shim, Yeong Seok; Heo, Junseok; Lee, Changjin; Yoon, Sung Cheol; Kim, Jong H.; Ko, Seo Jin (Advanced Functional Materials, 2023)
Near-infrared organic photodetectors (NIR OPDs) comprising ultra-narrow bandgap non-fullerene acceptors (NFA, over 1000 nm) typically exhibit high dark current density under applied reverse bias. Therefore, suppression of dark current density is crucial to achieve high-performance of such NIR OPDs. Herein, cyano (CN) with a strong electron-withdrawing property is introduced into alkoxy thiophene as a π-bridge to adjust its optoelectronic characteristics, and the correlation between dark current density and charge injection barrier is investigated. Compared with their motivated NFA (COTH), the novel CN-substituted NFAs, COTCN and COTCN2, exhibited deeper-lying highest occupied molecular orbital energy levels and narrower optical bandgap (<1.10 eV), owing to the strong inductive and resonance effect of CN. The dark current and total noise currents are minimized as the number of substituted CN increases because of the larger hole injection barrier. Consequently, PTB7-Th:COTCN2 exhibited the best shot-noise limited detectivity (D*sh, 1.18 × 1012 Jones) and total noise detectivity (D*n, 1.33 × 1011 Jones) compared with those of PTB7-Th:COTH (D*sh, 2.47 × 1011 Jones and D*n, 1.96 × 1010 Jones).
Keywords: Cyano substitution; Dark current densities; Detectivity; Low dark current density; Narrow bandgap; Near Infrared; Near-infrared; Non-fullerene acceptor; Organics; Ultra narrow bandgap; CN substitutions; low dark current densities; near-infrared; non-fullerene acceptors; ultra narrow bandgaps